2022
DOI: 10.1177/09540083221134955
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and microwave absorption studies on 2D graphitic carbon nitride loaded polyaniline/polyvinyl alcohol nanocomposites

Abstract: A light weight electromagnetic interference (EMI) shielding and microwave absorbing composite films has been developed by loading varying weight content of graphitic carbon nitride (g-C3N4) nanosheets and polyaniline (PANI) into polyvinyl alcohol (PVA) matrix. The prepared PVA/PANI/g-C3N4 (1%, 3%, 5%) composites has been subjected to FTIR, X-Ray powder diffraction, SEM, Thermal studies, Dielectric studies and electromagnetic shielding effectiveness (EMI SE) analysis. The PVA/PANI/g-C3N4 (1%, 3%, 5%) composites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Studies have shown that the incorporation of particle, fiber, or nanomaterial reinforcements into polymers can create polymer matrix composites with high performance and/or excellent functionals 23–25 . GNP is also a preferable conductive medium with superior thermal stability 26–28 . Similarly, related studies have shown that GNP has a direct effect on electromagnetic radiation shielding, 29,30 which suggests that GNP has promising applications in composite modification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the incorporation of particle, fiber, or nanomaterial reinforcements into polymers can create polymer matrix composites with high performance and/or excellent functionals 23–25 . GNP is also a preferable conductive medium with superior thermal stability 26–28 . Similarly, related studies have shown that GNP has a direct effect on electromagnetic radiation shielding, 29,30 which suggests that GNP has promising applications in composite modification.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] GNP is also a preferable conductive medium with superior thermal stability. [26][27][28] Similarly, related studies have shown that GNP has a direct effect on electromagnetic radiation shielding, 29,30 which suggests that GNP has promising applications in composite modification. The addition of graphene oxide (GO) is increasingly applied in polymer nanocomposites to tailor their properties further.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high-frequency electromagnetic waves (EM waves) like microwave and radio frequency influence are individual transmitted all around us as an outcome of the quick growth and meteoric increase in the electronic gadgets and their uses. [2][3][4][5][6] The primary goal of research on radar stealth materials is to enhance the absorption capabilities for EMWs in the X-band frequency range. 7 Due to the exponential expansion of smaller and more useful electronic devices, recent advancements in telephony and electronics have significantly worsened the electromagnetic interference (EMI) problem.…”
Section: Introductionmentioning
confidence: 99%
“…Humans benefit greatly from the use of electromagnetic waves (EMWs), which dominate wireless communication and detecting technology, and the threat from electromagnetic attack to defense is also very real. In addition, high‐frequency electromagnetic waves (EM waves) like microwave and radio frequency influence are individual transmitted all around us as an outcome of the quick growth and meteoric increase in the electronic gadgets and their uses 2–6 …”
Section: Introductionmentioning
confidence: 99%
“…Filling the conductive material into a flexible matrix is deemed to be a way to earn flexible EMI SE composites . In such a case, polystyrene, poly­(methyl methacrylate), poly­(vinyl alcohol), polyimide, polyurethane, polypropylene, epoxy resin, and poly­(vinylidene fluoride) (PVDF) are often used as the flexible matrixes, , and among them, PVDF is recommended due to its excellent flexibility, lightweight, processability, and dielectric properties . Therefore, many flexible EMI SE composites based on PVDF have been developed for potential practical applications. It is reported that the EMI SE performance of Ag/graphite/PVDF flexible composite films prepared by Kumaran et al via embedding Ag nanoparticles into graphite was measured to be 29.1 dB at 12.4 GHz .…”
Section: Introductionmentioning
confidence: 99%